JENIS POHON PENYUSUN DAN POLA PEKARANGAN DI DESA BANYUREJO, TEMPEL, SLEMAN, YOGYAKARTA - , VERA KUMALA DEWI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Agroforestry land management pattern that has long made by the villagers is the management of the yard. Implementation of agroforestry by village communities with a view to enhancing food needs, sufficient for firewood and construction timber, forage fodder, and to produce other products that can be sold. In this study using Census dilahan yard. The sample was divided into three zones, namely Zone A (ZonaTinggi) with a height of 200 m PDL., Zone B (Zone Medium) with a height of 190 m PDL., Zone C (Zone Low) with a height of 173 m PDL. For the purposes of the collection method and used inventory also aims to find out the name of tree species making up the yard. The result showed 42 species of trees of the family and all beberpa yard pick 2 of them are the most common type Nephellium lappaceum and Artocarpus heterophylla. Patterns found in the village yard Banyurejo is Random pattern mixture.